Pattern of occlusal contacts in eccentric position of mandible in dental students - Shrestha, K.; Shrestha, P.; Maskey, B.; Pradhan, R.; Poudel, S. (Journal of Nepalese Prosthodontic Society, 2021)
Introduction: Canine protection and group function are the two stand out occlusal schemes observed during laterotrusive movement of the mandible. The study aims to evaluate the frequency of these occlusal schemes in Nepalese dental students.Materials and methods: A cross-sectional study was conducted among dental students in People’s Dental College and Hospital, Kathmandu, Nepal after the ethical approval from PDCH-IRC. Sixty four undergraduate students aged 21-30 years, were examined for the occlusal contact patterns in lateral mandibular movements using 12μm shim stock. The data were analyzed using SPSS software (version 21)Result: On 1mm laterotrusive position on mandible, 43 subjects (67%) showed group function, 15 subjects (24%) canine guided and 6 subjects (9%) non specified occlusion. On 3mm laterotrusive movement, 31(48%) subjects showed group function and 27 subjects (42%) showed canine guided occlusal scheme. The most frequent mediotrusive contact was the second molar followed by the first molars during both 1mm and in 3mm excursionConclusion: Majority of occlusal schemes of the study population were group function followed by canine protection and non specified occlusion. Canine protected occlusion scheme was increased on 3mm lateral excursion. Most of mediotrusive side contact seen on 2nd molar on 1mm.